2013
DOI: 10.1155/2013/549486
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Appropriate Digital Hearing Aid for Low‐Resource Countries: A Case Study

Abstract: This paper reviews the development process and discusses the key findings which resulted from our multidisciplinary research team's effort to develop an alternative digital hearing suitable for low-resource countries such as Thailand. A cost-effective, fully programmable digital hearing aid, with its specifications benchmarking against WHO's recommendations, was systematically designed, engineered, and tested. Clinically it had undergone a full clinical trial that employed the outcome measurement protocol adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Designing and producing a brand new low-cost medical device (hearing aid or sound generator) could be the most effective option. For example, the WHO has taken a big step forward in extending its activities to the economic context of medical and assistive technology and focusing more on rehabilitation and community living [69] and the development of an alternative digital hearing suitable for low-resource countries [70].…”
Section: Clinical Need In the Implement Of In-ear Medical Devices In mentioning
confidence: 99%
“…Designing and producing a brand new low-cost medical device (hearing aid or sound generator) could be the most effective option. For example, the WHO has taken a big step forward in extending its activities to the economic context of medical and assistive technology and focusing more on rehabilitation and community living [69] and the development of an alternative digital hearing suitable for low-resource countries [70].…”
Section: Clinical Need In the Implement Of In-ear Medical Devices In mentioning
confidence: 99%
“…The first, Development: [12] are develop an pocket-type digital hearing is call PDN-01B, which suitable for lowresource countries such as Thailand and the cons: shape design was old fashioned but it was a good response from the users in rural areas.…”
Section: Fig 4 Review Of Hearing Aidsmentioning
confidence: 99%
“…The National Electronics and Computer Technology Center (NECTEC), a Thai governmental organization, developed body-worn aid, digital, programmable hearing aids and has been producing them since 2006. The first model, PDN-01B, also called P01, met the electro-acoustical test standards set by the International Electrotechnical Commission (IEC 60118–7) [ 14 ]. Clinical testing revealed that users were very satisfied at both 3, and 6 months regarding ease of communication and speech understanding in a moderately reverberant room and other environments with competing noise.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical testing revealed that users were very satisfied at both 3, and 6 months regarding ease of communication and speech understanding in a moderately reverberant room and other environments with competing noise. Hence, the P01 model indicated suitable for users with moderate to severe hearing impairment [ 14 ]. P01 was later modernized, giving it a similar look to a media player (model P02) (Fig.…”
Section: Introductionmentioning
confidence: 99%